METHODS OF FORMING COMPETENCIES IN APPLICANTS FOR THE SPECIALTY «CYBERSECURITY» WHEN PERFORMING A COURSE ASSIGNMENT IN THE DISCIPLINE «LOCAL NETWORKS» - Pakhomova, Victoria (SWorld-Ger Conference proceedings, 2023)
The methodology of «AttackDetectionLAN» for the formation of professional and subject competencies of applicants for the degree «Bachelor» in the specialty «Cybersecurity» in the course assignment in the discipline «Local Networks» is proposed: 1) obtaini